Construction of Indonesian Muslim Identity in Photo News in National Newspaper in Medan City - Muhammad Said Harahap; Syukur Kholil; Iskandar Zulkarnain (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The presence of news photos that appear in print media plays a role in providing strong and accurate information that can contribute creativity and ideas, able to communicate messages through information channels to a mass audience. The research method used in this study is qualitatively descriptive with Roland Barthes's semiotic approach. The results of this study suggest that the news of ramadan and homecoming photos that take place once a year is able to create the meaning of social construction of Indonesian Muslim identity simultaneously a full month brings a positive message through the delivery of messages of kindness at routine activities carried out by Muslims in Indonesia. The marking of denotations, connotations and myths of its nature is everywhere the news of ramadan and homecoming events has become a part of the daily life culture of Indonesian Muslims so that through the structure of meaning that is included in the news photos peritiwa Ramadhan and Mudik has become guidelines and guidance for people in obtaining information on the meaning of the sign of the information needed and desired after publicity became the headline of the National Newspaper in Medan, among others, The Analisa Newspaper and Waspada Newspaper.